2008
DOI: 10.1117/1.3033757
|View full text |Cite
|
Sign up to set email alerts
|

Multiple trains of same-color surface plasmon-polaritons guided by the planar interface of a metal and a sculptured nematic thin film

Abstract: The spin and the orbital angular momentums of multiple surface-plasmon-polariton (SPP) waves guided by a planar interface of a metal and a periodically nonhomogeneous sculptured nematic thin film (SNTF) were theoretically investigated in the canonical boundary-value problem. Both the Minkowski and the Abraham formulations of angular momentums were considered. Multiple SPP waves guided by the metal/SNTF interface in a direction obliquely with respect to the morphologically significant plane of the SNTF were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…The experimental observation of multiple SPR therefore confirms the theoretical predictions. [6][7][8][9] Comments on the angular location and width of SPR dips are discussed by Polo and Lakhtakia. 6 These resonant phenomenon could be used for sensing purposes such as detecting biomolecules of interest for water safety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental observation of multiple SPR therefore confirms the theoretical predictions. [6][7][8][9] Comments on the angular location and width of SPR dips are discussed by Polo and Lakhtakia. 6 These resonant phenomenon could be used for sensing purposes such as detecting biomolecules of interest for water safety.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, SPPs are excited at noble metal/homogeneous dielectric material interfaces and can be observed only for the parallel polarization of the incident laser beam, p-polarization (the direction of the polarization lies in the plane of incidence). 3 Recent theoretical studies [6][7][8][9] have shown that by replacing the homogeneous dielectric material by a linear, anisotropic dielectric material, more than one SPP wave can be launched, and in the same film SPP waves can also be observed for spolarization of the incident laser beam (the direction of the polarization is perpendicular to the plane of incidence). 6,7 The theoretical basis for the excitation of multiple SPR and excitation by s-polarization is explained by Faryad and Lakhtakia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitation of SPP waves with s-polarized light, in the case of chiral STF dielectric, may not be too surprising, since it might be argued that some conversion of s-polarization to p-polarization could occur because of the helical nature of the nanocolumns. This mechanism, however, can not be invoked to explain the results of calculations [3] which show that s-polarized light traveling parallel to the morphologically significant plane of the SNTF, at a metal/SNTF interface, can also excite a SPP wave.…”
mentioning
confidence: 77%
“…The number of modes of SPP-wave propagation observed depended on the periodicity of the chiral STF, with as many as four modes for a single metal/chiral STF interface. Later calculations [3,5] would reveal the same phenomenon at the interface of a metal and a periodic SNTF. In most cases, SPP waves could be observed, with an STF comprised of only two structural cycles, and, furthermore, the SPP waves were nearly identical to SPP waves calculated at the interface of semi-infinite expanses of metal and STF with an infinite number of cycles.…”
mentioning
confidence: 99%